ENGLISH SENIOR HIGH SCHOOL TEXTBOOK ANALYSIS: ADDRESSING GENDER BIAS ISSUES - Nashriyah, Nashriyah; Khairul, Dini (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2018)
Due to the imbalance gender presentation in English Senior High School textbook detected during teaching practice program, the researcher was interested in doing a research about the issue. Students might take much time to learn from textbooks to develop their gender roles at school, therefore, the proper textbooks which attain the objectives of gender equality are needed. The aim of this study is to investigate whether or not female and male are presented equally in the English Senior High School textbook. The object of this study is the English textbooks widely used by teachers in Banda Aceh Senior High School. First and second textbook entitled Bahasa Inggris X Semester 1 and Bahasa Inggris X Semester 2 were written by Utami Widyati, Zuliati Rohmah, and Furaidah in 2014. Third and fourth textbook entitled Bahasa Inggris XI Semester 1 and Bahasa Inggris XI Semester 2 were written by Mahrukh Bashir in 2014. The last textbook is Bahasa Inggris XII was written by Utami Widyati, Zuliati Rohmah, and Furaidah in 2015. All textbooks were published by Indonesian Ministry of Education and Culture. The focus of this study is the gender representation through five aspects which were also used by Amini and Parviz in their study in 2012. The five aspects are visibility, firstness, masculine generic construction, activity, and occupation. The result showed that four aspects were led by male in the term of quantity: visibility, firstness, masculine generic construction, and occupation while females were more visible in activity aspect. Even so, the difference of number was not too big in every aspect, except the visibility. However, in the term of quality, visibility and activity aspects showed that female and male are presented fair enough in English textbook at high school level by involving females in every aspect which may indicates that females are considered as important and useful as males nowadays.